1989
DOI: 10.1128/iai.57.12.3751-3756.1989
|View full text |Cite
|
Sign up to set email alerts
|

Strain variation in antiphagocytic activity of capsular polysaccharides from Cryptococcus neoformans serotype A

Abstract: Strains of Cryptococcus neoformans vary in resistance to phagocytosis in vitro. The binding of isolated capsular polysaccharide (CPS) to a capsule-free mutant of C. neoformans confers resistance to phagocytosis. The importance of capsule composition to differences among strains in susceptibility to phagocytosis was evaluated. CPSs from five strains of C. neoformans serotype A, designated 6, 15, 98, 110, and 145, which had previously been isolated and characterized as to molecular size, composition, and binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 24 publications
1
23
0
1
Order By: Relevance
“…In the case of C. neoformans , early studies demonstrated that the capsule inhibited phagocytosis (Kozel & Gotschlich, ). Supporting this role of the capsule, binding of isolated capsular polysaccharide to capsule‐free mutants conferred resistance to phagocytosis (Small & Mitchell, ). Thus, it is believed that the capsule acts as a physical barrier that impairs the recognition of phagocytic receptors with epitopes of the cell wall (Kozel & Gotschlich, ).…”
Section: Cryptococcus Neoformans Can Avoid Internalization By Macrophmentioning
confidence: 99%
“…In the case of C. neoformans , early studies demonstrated that the capsule inhibited phagocytosis (Kozel & Gotschlich, ). Supporting this role of the capsule, binding of isolated capsular polysaccharide to capsule‐free mutants conferred resistance to phagocytosis (Small & Mitchell, ). Thus, it is believed that the capsule acts as a physical barrier that impairs the recognition of phagocytic receptors with epitopes of the cell wall (Kozel & Gotschlich, ).…”
Section: Cryptococcus Neoformans Can Avoid Internalization By Macrophmentioning
confidence: 99%
“…A major mechanism by which the capsule seems to enable C. neoformans to subvert host defenses is by presenting a surface not recognized by phagocytes (149,172). Acapsular isolates are readily engulfed by phagocytes, possibly via man-nose and ␤-glucan receptors (56,147,181,247,267). In contrast, in the absence of opsonins, most phagocyte populations will not bind encapsulated strains of C. neoformans (19,147,149,172,181,183).…”
Section: Cryptococcus Neoformansmentioning
confidence: 99%
“…C. neoformans is unique among the fungi because it has a polysaccharide capsule composed mainly by glucuronoxylomannan (GXM) surrounding the cell that is a major virulence factor (Chang and Kwon‐Chung, 1994; Casadevall and Perfect, 1998; McFadden and Casadevall, 2001). The capsule makes C. neoformans resistant to phagocytosis such that in the absence of opsonins, phagocytic cells do not ingest yeast cells (Mitchell and Friedman, 1972; Kozel and Gotschlich, 1982; Kozel et al ., 1988a; Small and Mitchell, 1989). However, for C. neoformans , Abs also promote phagocytosis through CR3 and CR4 in the absence of C3 by a mechanism that involves a lectin‐like interaction between the capsular polysaccharide and CR3 and CR4 (Dong and Murphy, 1997; Netski and Kozel, 2002; Taborda and Casadevall, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…When C3 localizes deep inside the capsule, as occurs for cryptococcal cells with large capsules, C3 is not accessible to the receptor and the process is inefficient in promoting phagocytosis (Zaragoza et al ., 2003). Consequently, the efficiency of C‐mediated phagocytosis is critically dependent on the size of the capsule of the C. neoformans strain (Mitchell and Friedman, 1972; Kozel et al ., 1988b; Small and Mitchell, 1989; Yasuoka et al ., 1994; Zaragoza et al ., 2003). Recent studies show that another factor that influences C3 localization is the source of serum, with serum from different mammalian species in different regions of the capsule (Gates and Kozel, 2006).…”
Section: Introductionmentioning
confidence: 99%